Aesthetic approaches and their representations in calligraphic compositions (the Baghdad school - Yaqut Al-Mustasimi and his students as an example) (Al-Academy, 2023)
This research delves into the aesthetic approaches and representations within the realm of calligraphic compositions, with a specific focus on the Baghdadi School, under the tutelage of Yaqut Al-Mustasimi and his students. By examining the intricate relationship between concepts and their visual manifestations, the study seeks to elucidate the intrinsic meanings embedded in linear compositions and the textual representations that emerge from this dynamic interplay.Narrowing the scope to the exclusive exploration of calligraphy formations within the Baghdadi School, the theoretical framework, presented in the second chapter, not only introduces the Baghdad school and Yaqut al-Mustasimi's biography but also delves into various aesthetic concepts, encompassing philosophical, literary, and rhetorical elements and their interplay with textual data and composition.Three noteworthy findings emerged: first, the mutual interaction between conceptual themes and calligraphic text, leading to the creation of expressive and aesthetically rich dimensions firmly grounded in the principles and regulations of Arabic calligraphy. Second, the adaptive nature of letters, enabling them to gracefully conform to the constraints of specific texts and available space, effectively showcasing the textual data and its underlying significance, showcasing the dynamic evolution of Arabic calligraphy. Finally, the concept of improvisation, a cornerstone of the Baghdadi school, emphasizing simplicity as the foundation for mastery.The third chapter delves into the research methodology and the process of selecting formations, while the fourth chapter reviews key findings, notably emphasizing the sufficiency of letters and words in preserving their initial formal identity. Furthermore, it highlights the inherited characteristic of impromptu intonation, relying on the relative proportions and pen angles, which have been passed down through generations, shaping the essence of Baghdadi calligraphy.